1995
DOI: 10.1177/096032719501400511
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine compound residues in human milk in the United Kingdom 1989-1991

Abstract: 1 The concentrations of some organochlorine pesticides and polychlorobiphenyls have been determined in 193 samples of human milk collected between July 1989 and July 1991. 2 Comparison of the results with those from previous studies in 1979-80, and earlier, shows a continuing decline in residue levels except for polychlorobiphenyls. 3 The concentrations of organochlorine pesticides and polychlorobiphenyls in human milk samples from resi dents in the United Kingdom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…Heptachlor epoxide levels in the present study are similar to or lower than those seen in recent large studies from the Netherlands (15) and Germany (33,34). Dieldrin levels seen here are similar to or lower than those seen in the Netherlands (15), Germany (13), and the United Kingdom (14). Endrin is seen in a minority of samples in this study, which is similar to most other reports (1).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Heptachlor epoxide levels in the present study are similar to or lower than those seen in recent large studies from the Netherlands (15) and Germany (33,34). Dieldrin levels seen here are similar to or lower than those seen in the Netherlands (15), Germany (13), and the United Kingdom (14). Endrin is seen in a minority of samples in this study, which is similar to most other reports (1).…”
Section: Discussionsupporting
confidence: 86%
“…The ,B-HCH concentrations seen in this study, with a median of 731 ng/g milk fat, are high compared to those seen in other reports from Europe. Recent large studies, for example, reported 3-HCH concentrations (in nanograms per gram of milk fat) of 64 in 1990 and 56 in 1991 from Germany (13); a median of 60 from the United Kingdom (14); and a median of 80 from the Netherlands (15). Hernandez et al (16) reported a mean of 235 ng/g milk fat; this is among the highest previously reported from Europe.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore burden of these pesticides in mother's body can be indicative of route of these pesticides to the infants. Many investigations in different countries have reported contamination of breast milk with DDT and other organochlorine pesticides (Dwarka et al, 1995;Cok et al, 1997;Schinas et al, 2000;Yang et al, 2002;Yu et al, 2003). Studies carried out in various other states of India like Panjab, Hariyana, Uttar Pradesh and Tamil Nadu showed that the human milk is contaminated with a fairly high amount of Organochlorine pesticide residues like DDT, HCH, aldrin and endosulfan.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, seven PCB congeners (IUPAC Nos. 28,52,101,118,138,153,and 180) were selected as indicator compounds to monitor occurrence and distribution (Dwarka et al 1995;Schoula et al 1996;Pauwels et al 2000). Concentrations of PCB 52 and PCB 180 in infertile subjects were found higher then fertile subjects ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%